QARAQALPAQ XALÍQ QOSÍQLARÍNÍŃ RAWAJLANÍWÍNDA KOMPOZITOR Ǵ.AMANIYAZOVTÍŃ TUTQAN ORNÍ - Eshbaeva, G. (SCIENCE and SOCIETY, 2024)
This article examines the role of the composer G.Amaniyozov in the development of Karakalpak folk songs and his close connection with the life of the people.
Keywords: art; culture; creativity; composer; folk song; genre; folk tradition